A case report: spontaneous postpartum rupture of unscarred uterus - Singh, Swati; Ahlawat, Ravinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Rupture of uterus is characterized by a breach in the wall of the uterus involving its full thickness. An unscarred uterus rupture is uncommon. It has non-specific symptoms and presentation differs according to site and time of rupture. Authors report an unusual case of spontaneous rupture of unscarred uterus. A 32-year-old, pregnant woman, developed postpartum bleeding with no history of prior uterine incision. She was diagnosed as a case of rupture of uterus and emergency laparotomy was done. Early diagnosis and immediate surgical intervention may significantly improve the prognosis. Differential diagnosis of uterine rupture should always be kept in mind in all patients with or without risk factors.